Silicon Valley Start‐ups and Corporate Innovation Approaches to Resolve the Innovator's Dilemma - Gold, Bernhard (Markt- und Unternehmensentwicklung Markets and Organisations, 2018)
Bernhard Gold answers the question of how larger firms can learn from the successes of Silicon Valley start-ups by means of corporate venturing and by developing the 'Spin-Along Approach' - a method that combines the innovativeness of start-up companies with the capabilities of large corporations to obtain the best of both worlds. Moreover, the author provides an in-depth analysis of the Silicon Valley ecosystem and presents new corporate innovation methods for the digital age, with the aim of providing a final resolution to the 'Innovator's Dilemma'. Contents Start-up Innovativeness and Corporate Venturing The Spin-Along Approach Success Factors of Silicon Valley The Concept of Intra-Nationalization Target Groups Researchers and students of business administration, strategic and innovation management, organizational theory, (corporate) venture capital, business ecosystems, internationalization Members of top management, innovation management, venture capital, finance, business development, corporate development, M&A The Author Bernhard Gold lives and works as a venture capitalist in Silicon Valley (San Francisco). Over the last ten years, he has invested in many Silicon Valley companies and thus has intimate knowledge of the intersection between start-ups and the corporate world. Gold completed this dissertation project at the Munich School of Management of the Ludwig-Maximilians-University of Munich (LMU). .